Pengaruh Pengalaman Kerja, Pendidikan dan Pelatihan (Diklat) terhadap Pengembangan Karier pada PT. BPRS PNM Mentari Garut - Rohimat Nurhasan (Fakultas Ekonomi Universitas Garut, 2017)
This study aims to determine empirically about the effect of work experience and training on career development at PT. BPRS PNM Mentari Garut. The data used in this study are primary and secondary data. Primary data in the form of questionnaire results distributed to 34 respondents at PT. BPRS PNM Mentari Garut. Secondary data is in the form of company profile data, training conducted in the company, employee tenure, etc. The independent variables used in this study are Work Experience and Education and Training, while the dependent variable in this study is Career Development. The data analysis technique used in this research is descriptive analysis and verification with the tools of the SPSS 20.0 program. Hypothesis testing uses Multiple Linear Regression. The results showed that: (1) there is a significant direct influence between Work Experience and Career Development variables. (2) there is a significant direct influence between the variables of Education and Training on Career Development. (3) there is a significant direct influence between Work Experience and Training and Education variables on Career Development.